Peningkatan Hasil Belajar Biologi Menggunakan Model PBL (Problem Based Learning) dengan Media Lingkungan - Yusuf, Moh; Pujiastutik, Hernik (Universitas Sebelas Maret, 2017)
The purpose of the study is to improve student learning outcomes by using model of Problem Based Learning in the Environment. The research method is classroom action research with the stages of each cycle, namely planning, implementation, observation, and reflection. In this study using 2 cycles because it has obtained good results while the data collection techniques using non tests and tests. Data analysis techniques used qualitative and quantitative analysis. The results showed that the application of PBL model (Problem Based Learning) with environmental media can improve student learning outcomes. The increase is evidenced by the learning outcomes in cycle I obtained an average percentage value of 85% and increased in cycle II to 95%. Improved student learning outcomes using PBL (Problem Based Learning) learning model with environmental media belonging to the category of